Adaptive array antenna design for wireless communication systems - Nurul Hazlina, Noordin (2013)
Adaptive array antennas use has been limited to non-commercial applications due to their high cost and hardware complexity. The implementation cost of adaptive array antennas can be kept to a minimum by using cost effective antennas, reducing the number of elements in the array and implementing efficient beamforming techniques. This thesis presents techniques for the design of adaptive array antennas which will enable their cost effective implementation in wireless communication systems. The techniques are investigated from three perspectives, namely, reconfigurable antenna design, wide scan array design and single-port beamforming technique. A novel single-feed polarisation reconfigurable antenna design is proposed in the first stage of this study. Different polarisation states, namely, linear polarisation (LP), left-hand circular polarisation (LHCP) and right-hand circular polarisation (RHCP), are achieved by perturbing the shape of the main radiating structure of the antenna. The proposed antenna exhibits good axial ratio (< 3 dB at 2.4 GHz) and has high radiation efficiency in both polarisation modes (91.5 % - LHCP and 86.9 % - RHCP). With a compact single feeding structure, the antenna is suitable for implementation in wireless communication devices. The second stage of the study presents the design procedure of wide scan adaptive array antennas with reduced number of elements. Adaptive array antennas with limited number of elements have limited scanning range, reduced angular scanning resolution and high sidelobe levels. To date, design synthesis of adaptive array antennas has been targeted on arrays with a large number of elements. This thesis presents a comprehensive analysis of adaptive array antennas with less than 10 elements. 'Different array configurations are analysed and various array design parameters such as number of elements, separation between elements and orientation of the elements are analysed in terms of their 3 dB scan range. The proposed array, the 3-faceted array, achieves a scanning range up to ±700, which is higher than ±56° obtained from the Uniform Linear Array. The faceted arrays are then evaluated in the context of adaptive beamforming properties. It was shown that the 3-faceted array is suitable for adaptive array applications in wireless communication systems as it achieves the highest directivity compared to other faceted structures. The 3-faceted array is then synthesised for low sidelobe level. Phase correction together with amplitude tapering technique is applied to the 3-faceted array. The use of conventional and tuneable windowing techniques on the 3faceted array is also analysed. The final stage of the study investigates beamforming techniques for the adaptive array antenna. In the first part, beamforming algorithms using different performance criteria, which include maximum signal-to noise-ratio (SINR), minimum (mean-square Error) MSE and power minimisation, are evaluated. In the second part, single-port beamforming techniques are explored. In previous single-port beamforming methods, the spatial information of the signals is not fully recovered and this limits the use of conventional adaptive beamforming algorithms. In this thesis, a novel signal estimation technique using pseudo-inverse function for single-port beamforming is proposed. The proposed polarisation reconfigurable antenna, the 3-faceted array antenna and the single-port beamforming technique achieve the required performance, which suggests the potential of adaptive array antennas to be deployed commercially, especially in wireless communication industry.